Evaluating Learning Management System based on PACMAD Usability Model: Brighten Mobile Application - Faudzi M.A.; Cob Z.C.; Omar R.; Sharudin S.A. (Science and Information Organization, 2023)
Computer aided instruction; E-learning; Learning systems; Mobile computing; Cognitive loads; Learning management system; Learning process; Mobile application development; Mobile applications; Mobile Learning; Moodle; Pacmad; Traditional learning; Usability models; Usability engineering